Ankle: Proprioceptive exercises balance rehabilitation - Kawaguchi, J. (1999)
These activities are by no means intended to be an all-inclusive list for rehabilitation following an ankle injury, but hopefully we have introduced some concepts concerning proprioceptive activities and how they can be incorporated as part of a successful rehabilitation process. Not all aspects of a successful rehabilitation have been covered here, since the focus was on the role of balance and proprioception. Other areas to consider include foundational strength and how it applies to the appropriate introduction of power and agility, as well as restoration of both cardiovascular and muscular endurance. Finally, an area of continued controversy requiring more research is whether any actual physiologic changes take place with proprioceptive exercises, or if all adaptations occur in other areas, which allow the athlete to compensate for some loss of neural input.